Peningkatan Kesejahteraan Ekonomi Keluarga Melalui Industri Kopi Rumahan - Azra, Uliya; Saifullah (JIMEBIS: Scientific Journal of Students Islamic Economics and Business, 2023)
This study aims to find the roles, supporting factors and inhibiting factors of the home coffee industry in increasing the economic welfare of working families and the community around the Malem Diwa home industry. The type of research used in this research is qualitative research. In collecting data researcher used direct interview methods. Based on the results of the study, it shows that the role of the Malem Diwa home coffee industry is able to increase family economic welfare, and can open jobs for the community around the home industry, so that people earn income to prosper the family economy in meeting family needs. Factors supporting the Malem Diwa home industry are sources of business capital from owners, labor, goods quality raw materials and technology. While the inhibiting factors are constrained by the lack of business capital and infrastructure facilities in supporting the activities of managing the home coffee industry.